UV-responsive CCD image sensors with enhanced inorganic phosphor coatings. - Franks, W.A.R (IEEE Transactions on electron devices)
Typical polysilicon gate charge-coupled device (CCD) image sensors are unresponsive to ultraviolet (UV) light because of the high absorption of the radiation in polysilicon gate material, which leads to a short penetration depth (<2 nm), and absorption of the radiation in the gate material rather than within the channel of the CCD. An inorganic phosphor coating to convert the UV radiation to visible has been developed. Although the coating is similar to acrylics doped with organic laser dyes reported previously, in this work the organic dye has been replaced with a more robust inorganic phosphor. In addition, a new deposition method has been developed to improve the photoresponse nonuniformity (PRNU) of the coated sensor. The inorganic phosphor has been selected over organic laser dyes because organic molecules degrade rapidly upon exposure to UV radiation, with exponential degradation rates as high as 3% per hour at an illumination level of 1 μW/cm2. Inorganic phosphors exhibit reduced degradation with 90% of the degradation occurring within the first 2% of the material's lifetime. It is this stabilization that improves the viability of phosphor-coated CCD image sensors for commercial applications. The quantum efficiency observed was 12% at 265 nm. The improved deposition technique reduced the photoresponse nonuniformity degradation fourfold, so the observed PRNU was only 0.4 times greater than that of the uncoated sensor.